Uma análise das interações discentes em fóruns de discussão online de ambientes virtuais de aprendizagem através da análise de redes sociais - Silva, Jarbele Cássia da (2015)
The development of studies on education distance learning courses or e-learning, have become common in the current academic-scientific assumption, as the increasing number of courses in this category of education and the possibilities of collaboration between participants brought by the Environment Virtual Learning (AVA). Online discussions established make students engaged in the sharing of information and knowledge, in order to establish prospects for interaction with other students. In this sense, this work aims to investigate the potential generated by the use of Social Network Analysis techniques (ARS) applied to the analysis of the interactions between students of a distance learning course that establish communication in online discussion forums, to ascertain patterns of interaction that may have influence on student learning. The results show that by applying the degree of centrality metrics, centrality intermediation and closeness centrality related to student achievement express a linear correlation between such variables, showing a trend in the performance of the same throughout the course in order to provide teachers information to support the development of strategies for monitoring and management of student learning in distance learning courses.